A Quantitative Study on Writing Anxiety among Prospective English Language Teachers - Alprince King A. Biri (Researchparks Publishing, 2022)
Writing is a critical skill that must be acquired by the students to be able to learn the language and for academic success. Since writing is widely recognized as a challenging task for ESL learners during the teaching and learning processes, students tend to face certain concerns that inhibit them from performing well in writing activities, one of which is anxiety. Writing anxiety is a catch-all term for a range of negative feelings toward writing. The purpose of the current study is to investigate the level, type, and cause of writing anxiety of the 95 prospective English language teachers. The study also endeavored in finding out the significant difference in the level, type, and cause of writing anxiety when respondents are clustered according to gender and year level. Data were obtained using two instruments namely: Second Language Writing Anxiety Inventory (SLWAI) and Cause of Second Language Writing Anxiety Inventory (CLAWI) developed by Cheng (2002) and Rezaei and Jafari (2014) respectively. In addition, data were statistically analyzed using descriptive analysis. Results revealed that the overall levels of writing anxiety among the respondents exhibit a moderate level of anxiety. Further, Cognitive anxiety is the most dominant type of anxiety encountered by the respondents when prompted to write English compositions. Meanwhile, the major cause of writing anxiety of the respondents is fear of evaluation and negative comments from the teacher. Finally, results also revealed that there is no significant difference in the level, type, and cause of writing anxiety across gender and year levels.